The Adoption of the 'Buruan Sae' Agricultural Extension Application in Bandung City Using the UTAUT - Tsabitul Azmi, Hilmi; Utomo, Rio Guntur; Nuha, Hilal H.; Yasirandi, Rahmat (My University, 2023)
The 'Buruan Sae' program in Bandung is an integrated urban farming initiative by the Department of Food and Agriculture. This research investigates the factors influencing the adoption of the agricultural extension application 'Buruan Sae' in Bandung City, utilizing the UTAUT model. The study collected data from 14 agricultural extension agents working under the Department of Food Security and Agriculture. The analysis identified trust and performance expectancy as the key determinants of adoption, complemented by attitude and dependence. The study investigated the impact of different factors on users' intention to use the 'Buruan Sae' app. The study investigated the impact of UTAUT variables on Behavioral Intention towards the 'Buruan Sae' app. Four out of five variables (Effort Expectancy, Social Influence, Facilitating Conditions, and Perceived Technology) positively influenced Behavioral Intention, while Performance Expectancy had a weaker impact. The Performance Expectancy's regression coefficient was 0.410 with a significance level of 0.000 $( < 0.05)$, leading to the acceptance of Hypothesis 1. The same holds true for Effort Expectancy and Social Influence with t-values of 6.013 and 3.668, respectively, both significant at sig $< 0.05$, confirming Hypotheses 2 and 3. Facilitating Conditions' influence on Perceived Technology was established with a t-value of 5.425 and sig $< 0.05$, accepting Hypothesis 4. The F-test further supported the impact of Performance Expectancy, Effort Expectancy, Social Influence, and Facilitating Conditions on Perceived Technology, as Hypothesis 5 was accepted due to a sig of 0.002 and a calculated F-value of 10.296 $( > 3.59)$. The study concludes that due to limitations in the data, further research is recommended for a more thorough exploration of how 'Buruan Sae' app is used by extension workers in the Food and Agriculture Resilience Agency. This could involve methods like direct observations, interviews, or case studies to gain insights into farmers' use of the app, along with the associated challenges and benefits.
Keywords: Bandung; IT Adoption; Urban Farming; UTAUT